2022
DOI: 10.3390/ijerph192114039
|View full text |Cite
|
Sign up to set email alerts
|

Helping Women Suffering from Drug Addiction: Needs, Barriers, and Challenges

Abstract: Statistical data on the use of various psychoactive substances indicate a narrowing of previous differences in substance use between men and women. Data from studies conducted among women suffering from drug addiction are increasingly published, with the authors highlighting the specific needs of this group and the difficulties that women with addiction problems encounter. The current study aimed to identify the barriers and needs of this audience, both when seeking help and during treatment. The method used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
0
10
0
3
Order By: Relevance
“…The socio-economic vulnerability may increase risk-taking, high-risk IDU, limited treatment-seeking, and poor treatment engagement. [ 4 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The socio-economic vulnerability may increase risk-taking, high-risk IDU, limited treatment-seeking, and poor treatment engagement. [ 4 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study on women's substance use supports this gender difference in separation rate. [ 8 ] Women with substance use encounter higher social stigma, domestic violence, and less family support across the globe, especially in developing countries like India. [ 7 8 10 ] Six out of seven cases lacked family support, and four of them did not follow up after the initial visit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research could also help understand the barriers for young women with drug addictions and psychedelics. Marek et al’s (2022) study found that Polish females faced limited support and stigma-related challenges [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%